Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan di CV. Yon Mitra Abadi - Usran Masahere; Tri Lestari; Selly Tri Rosanti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine the effect of work motivation and discipline on work productivity at CV Yon Mitra Abadi, a company procuring goods and services. The study involved 45 respondents using a saturated sampling technique. The method used is quantitative, with data collected through research instruments and data analysis conducted using SPSS 27. The analysis results show that work motivation does not significantly affect employee productivity (count 1.220 < table 2.018, significance 0.229 > 0.05). However, work discipline has a positive and significant effect on productivity (tcount 2.118 > ttable 2.018, significance 0.040 < 0.05). Simultaneously, motivation and work discipline together have a positive and significant impact on work productivity (Fcount 102.491 > Ftable 3.22, significance 0.050 < 0.05). This study shows that work discipline has a greater influence on increasing productivity compared to motivation.